2004
DOI: 10.1111/j.1365-2729.2004.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and remedial learning strategy based on conceptual graphs

Abstract: Numerous scholars have applied conceptual graphs for explanatory purposes. This study devised the 'Remedial-Instruction Decisive path (RID path)' algorithm for diagnosing individual student learning situation. This study focuses on conceptual graphs. According to the concepts learned by students and the weight values of relations among these concepts, this study established the remedial-instruction paths to identify their real missing concepts. This study applies diagnostic and remedial learning strategies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…It has been observed that for P-Learning general data mining algorithms like Apriori [34,50], DHP [33,54], SPRT [47] have been used for concept map computation. For C-Learning concept maps have been constructed based on discussion between the learners [57,59,61] and thus EDM techniques have not been used.…”
Section: Summary Of Edm Algorithmic Aspectsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been observed that for P-Learning general data mining algorithms like Apriori [34,50], DHP [33,54], SPRT [47] have been used for concept map computation. For C-Learning concept maps have been constructed based on discussion between the learners [57,59,61] and thus EDM techniques have not been used.…”
Section: Summary Of Edm Algorithmic Aspectsmentioning
confidence: 99%
“…al. [47] suggests two main applications of concept maps. In the first type of applications, students learn a subject and construct concept maps based on it.…”
Section: Concept Map Based Web Learning Systems Developed Using Edm Tmentioning
confidence: 99%
See 2 more Smart Citations
“…As known, to improve students' learning performance, the teacher should give them additional suggestions. However, it is time consuming for him to give personalized suggestions to each student, particularly when there are many students in class [1,16].…”
Section: Introductionmentioning
confidence: 99%